If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 119 + -4x = 23 + 20 Combine like terms: 23 + 20 = 43 119 + -4x = 43 Solving 119 + -4x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-119' to each side of the equation. 119 + -119 + -4x = 43 + -119 Combine like terms: 119 + -119 = 0 0 + -4x = 43 + -119 -4x = 43 + -119 Combine like terms: 43 + -119 = -76 -4x = -76 Divide each side by '-4'. x = 19 Simplifying x = 19
| ln(7x-3)=3 | | 8x-32y=64 | | 4(3x+2)+4=9x+3 | | 17x-8y=323 | | 3ab+7ab-ab= | | 6-9x=14-6x | | 4x^2-x+7=7x+4 | | -9*9= | | 9*-9= | | (3x+52)=36 | | 58-6x=7x | | 6x+12=3(2x+4) | | 9y+3-5y=23 | | 6t-14=-10+5t | | 4x+8-12x=5x-(3x+2) | | 3q^2+4q=-2 | | 2x-6y=24whatisy | | 9m+18= | | 2x-6y=24 | | 3t-24=-24+8t | | 9x+7=6x+2 | | -4(8w-7)=-30w+10 | | 6-y=25 | | 3x^2-24x=-2x^2-7x-6 | | 4x+6=-12 | | 3x+25=61 | | 90-2x=80-x | | 8*-7+3=5*-7-18 | | x+2+3=270 | | 5x+48+7x=12(x-4) | | y^2-10y+25=3-x | | (9x+2)(3x^2-20x-7)=0 |